My Problems Are Solvable: Idiographic Methods Offset Age Differences in Interpersonal Problem Solving Among Young, Middle-Aged, and Older Adults - Artistico, Daniele; Cervone, Daniel; Garcia, Carolina Montes (Frontiers in Psychology, 2019)
This study tested the hypothesis that older adults retain high levels of everyday problem solving performance when confronting problems of maximal ecological relevance to their age group. Young, middle-aged, and older adults completed a daily challenge questionnaire in which they reported problems of maximal personal relevance (“idiographic problems”). We then assessed performance on an everyday problem-solving task in which participants generated solutions for idiographic problems relevant to their age group as well as problems generated by group matched research participants representing each of two other age groups (e.g., older adults received their own problems plus problems generated by matched younger and middle-aged adults). Performance was measured by solution fluency or total number of safe and effective solutions provided. Results fully supported our hypothesis; adults of all ages showed higher performance when solving their age-relevant idiographic problems.